2016
DOI: 10.14419/ijans.v5i2.6171
|View full text |Cite
|
Sign up to set email alerts
|

Nurses experience of communication with palliative patients in critical care unit: Saudi experience

Abstract: Communication is crucial regardless of a patient's condition in Critical Care Units (CCU). However; communication barriers are common in CCU. In recent years there has been a rapid growth within hospital settings in the provision of palliative care according to patient needs. The purpose of the research study was to investigate nurses' experiences of communication with palliative patients in CCU. A cross sectional design was conducted using questionnaire. The study sample included nurses who were working in CC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…this result was supported by El-Nagar and Lawend (2013) [23] who stated in a study about" Impact of Palliative Care Education on Nurses' Knowledge, Attitude and Experience regarding Care of Chronically Ill Children "that most of the sample had bachelor degree, also more than one quarter of them had experience ranged from 5-10 years. On the other hand, this result was in contrary with Alshehri and Ismaile (2016) [24] who reported in their study about "nurse's experience of communication with palliative patients" that the majority of nurses had a diploma level in nursing. The level of experience of the target respondents can be described as novice, and work without experience and background.…”
Section: Discussioncontrasting
confidence: 69%
“…this result was supported by El-Nagar and Lawend (2013) [23] who stated in a study about" Impact of Palliative Care Education on Nurses' Knowledge, Attitude and Experience regarding Care of Chronically Ill Children "that most of the sample had bachelor degree, also more than one quarter of them had experience ranged from 5-10 years. On the other hand, this result was in contrary with Alshehri and Ismaile (2016) [24] who reported in their study about "nurse's experience of communication with palliative patients" that the majority of nurses had a diploma level in nursing. The level of experience of the target respondents can be described as novice, and work without experience and background.…”
Section: Discussioncontrasting
confidence: 69%
“…Hospitals that involve nurses in decision‐making related to nursing issues and support high‐quality open communications between physicians and nurses are frequently considered highly attractive and motivated hospitals that have an exceptional ability to retain staff . To attain more knowledge and master new skills, nurses are always looking for more educational opportunities and professional development, and this, without any doubt, acts as an enormous motivation factor for them .…”
Section: Literature Reviewmentioning
confidence: 99%
“…There are many barriers to adherence to drug administration guidelines, including the failure to put evidence‐based research into practice, lack of support, poor communication among multidisciplinary teams and a working environment that does not support the culture of safety . In addition, nurses have reported that difficulty in reading handwritten orders, confusion about medications with similar names and lack of knowledge about patients’ medication allergies are contributory factors to MAEs .…”
Section: Introductionmentioning
confidence: 99%